An annotated list of diseases, pathogens and associated fungi of the common bean (Phaseolus vulgaris) in Eastern and Southern Africa - Allen, David J. (CAB International, 1995)
This list brings together many widely scattered unpublished records, from the International Mycological Institute, from the Centro Internacional de Agricultura Tropical, and from field surveys, conducted during recent collaborative research between CIAT and Horticulture Research International, Wellesbourne, and the Institute for Biochemistry and Plant Virology, Braunschweig. The literature survey has been extensive but probably not exhaustive : both recent and old checklists of published information have been scanned to provide an historical perspective to the presence of pathogens within a given territory. The list is confined to pathogens and diseases recorded on the common bean (Phaseolus vulgaris L.) in 20 countries of eastern, central and southern Africa and its off-shore islands. Information is given on their prevalence and pathogenic variability, with a comprehensive bibliography of more than 150 references. The list should prove valuable to plant pathologists, bean scientists, plant quarantine officers and research directors concerned with crop improvement and the international exchange of genetic resources.